Perubahan pengetahuan penjamah makanan hotel setelah penyuluhan higiene perorangan - Kusuma, Hapsari Sulistya; Pasanda, Amalia; Nugraheni, Kartika; Nissa, Choirun (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2017)
Background : Personal hygiene food handlers in food processing is very important because with the application of good hygiene can minimize the possibility of food contamination. The personal hygiene can be influenced by some factors, for instance knowledge and behaviors of food handlers. Lack of knowledge, inappropriate behaviors towards personal hygiene can be changed by giving the right information. Objective : This study aims to determine differences in knowledge of food handlers before and after counseling.Methods : This was a quasi-experimental one group pretest posttest design. The sample of this study was 18 food handlers in Patra Jasa Hotel selected by total sampling method. Knowledge data obtained from the total score from the correct answer in the questionnaire. The data was analyzed using Wilcoxon test.Results : This study showed that the increases in knowledge of food handlers increased by 22%. Statistical analysis showed knowledge before and after nutrition extension (p = 0.001).Conclusions : there was difference in knowledge of food handlers before and after personal hygiene counseling.